Effect of agglomerate size on extrudability of titania pastes. (July 2015) - Nicodemi, F.; Haber, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Pastes prepared from three high surface area titania powders were tested via torque and capillary rheometry to explain the different flow behaviour during mixing and extrusion processing. The Benbow analysis was used to calculate the main extrusion parameters, including bulk yield and shear stresses, and to compare the processability of the extrudable pastes. A critical water fraction was found for all powders and related to extrudability. The results show that the flow properties of the pastes are strongly influenced by the particle size distribution and the shear stability of large aggregates of different dimensions in the paste microstructure.